Writing, reading, choosing Africa. The mechanisms of reception and consecration of contemporary writers from the French-speaking countries of sub-Saharan Africa - (:unkn) unknown (My University, 2012)
Spanning the social sciences and the humanities, this dissertation explores themechanisms by which contemporary writers from Francophone sub-Saharan Africa attainliterary recognition. The empirical material comprises interviews with writers, publishers, andcultural agents; ethnographic observations of cultural events; archives (including letters writtento two writers); and a statistical survey of 404 writers who were socialized in this part of theworld, and who were active between...
Keywords: African Research